Superior layer-by-layer deposition realizing P–i–N all-polymer solar cells with efficiency over 16% and fill factor over 77%. Issue 20 (25th April 2022) - Li, Qingduan; Jia, Tao; Wang, Li-Ming; Liu, Shengjian; Liao, Xiaolan; Cao, Zhixiong; Zhang, Jiabin; Zhan, Xiaozhi; Zhu, Tao; Cai, Yue-Peng; Huang, Fei
Abstract : Considering the strong intermolecular interaction in all-polymer solar cells, 1-chloronaphthalene assisted layer-by-layer deposition was used to fabricate all-polymer solar cells with a P–i–N heterojunction and favorable crystallinity. Abstract : Although all-polymer solar cells (all-PSCs) possess merits like mechanical flexibility, the photovoltaic performance is still modest due to (i) the strong intermolecular interaction of the polymer donor–polymer acceptor and thus (ii) the extremely complicated morphology control. In this concise contribution, layer-by-layer (LBL) deposition is employed to fabricate high-performing all-PSCs reaching a remarkably enhanced efficiency of 16.1% with an improved fill factor (FF) of 77.3%. The neutron reflectivity studies show that the 1-chloronaphthalene (CN) solvent additive can facilitate the polymer acceptor diffusing into the underlying polymer donor layer, especially providing useful leverage for realizing a P–i–N heterojunction. Taking advantage of the independent coating of the donor and acceptor, the LBL photoactive layers are found to show good crystallinity. Surprisingly, efficient charge separation, transportation and extraction, and suppressed charge recombination are achieved in the optimized all-PSCs. Here we note that the LBL all-PSCs outperform the bulk heterojunction (BHJ) all-PSCs, and the FF of 77.3% achieved in this work is the highest among efficient all-PSCs. This contribution paves the way for realizing optimal morphology and high-performing all-PSCs.